Projected impact of a reduction in sugar-sweetened beverage consumption on diabetes and cardiovascular disease in Argentina: A modeling study - Salgado, Maria Victoria (2020)
Fil: Salgado, María Victoria. CEDES. Centro de Estudios de Estado y Sociedad. Área de Salud, Economía y Sociedad; Argentina.